A review of the anti-diabetic potential of saffron. (July 2022) - Sani, Anis; Tajik, Ali; Seiiedi, Seiied Sina; Khadem, Razieh; Tootooni, Haniye; Taherynejad, Mohammadhossein; Sabet Eqlidi, Nasim; Alavi dana, Seyyed mohammad matin; Deravi, Niloofar
Diabetes mellitus is one of the most prevalent metabolic disorders that affect people of all genders, ages, and races. Medicinal herbs have gained attention from researchers and have been widely investigated for their antidiabetic potential. Saffron ( Crocus sativus L.) and its main constituents, that is, crocin and crocetin, are natural carotenoid compounds, widely known to possess a wide spectrum of properties and induce pleiotropic anti-inflammatory, anti-oxidative, and neuro-protective effects. An increasing number of experimental, animal and human studies have investigated the effects and mechanism of action of these compounds and their potential therapeutic use in the treatment of diabetes. This narrative review presents the key findings of published clinical studies that examined the effects of saffron and/or its constituents in the context of diabetes mellitus. Moreover, an overview of the proposed underlying mechanisms mediating these effects, the medicinal applications of saffron, and the new findings regarding its effect on diabetes and various cellular and molecular mechanisms of action will be debated.